Rancang Bangun Sistem Pengecekan Peralatan Laboratorium Menggunakan RFID - Dian Ariyanto (UIN Sunan Kalijaga Yogyakarta, 2023)
Laboratory equipment used for calibration testing and/or practicum processes must go through a checking process so that the equipment meets standard specifications and can be used without any problems. The process of checking the equipment requires a process of documenting the process of checking laboratory equipment. The documentation process for checking equipment sometimes still uses paper forms and is filled in manually. The process of using paper forms has several drawbacks, so a laboratory equipment checking system is needed in the form of digital documents and is easy to use. Making the design of a laboratory equipment checking system through four stages, namely literature study, tool design, tool manufacture and tool realization. This checking system consists of three parts, namely RFID tags on laboratory equipment, RFID readers for reading RFID tags and Google sheets for storing data from RFID reader readings and recording the process of checking the device. From the results of this study, the minimum reading distance of the RFID reader to the RFID tag is 3 cm and the RFID reader is able to read the data contained in the RFID tag placed on laboratory equipment and send it to Google sheets.